Factors Affecting the Success Rate of Renal Stone Treatment by Extracorporeal Shock Wave Lithotripsy (Bangladesh Medical Journal, 2019)
ESWL is one of the treatment modalities for kidney stones smaller than 2 cm. However, not all ESWL treatments are successful. The success rate has been reported to be between 50% to 87%, depending on various factors. This study was conducted to evaluate factors affecting the success rate of renal stone treatment by extracorporeal shock wave lithotripsy (ESWL). The study was carried out for a period of one year where total 96 patients with single or multiple radio-opaque renal stones treated with ESWL monotherapy using Stortz Modulith SLX-F2 lithotriptor were included. The results of treatment were evaluated after 3 months of follow-up. Treatment success was defined as complete clearance of the stones or presence of clinically insignificant residual fragments (